(631) Statistical Analysis of Price System in Mainland China التحليل الإحصائي لنظام الأسعار في البر الرئيسي للصين - Mizoguchi, Toshiyuki (INP, 2024)
This paper aims to analyze price data in Mainland China and establish the characteristics of the price system through an international comparison. The data on commodity prices examined in Section 1 includes both official information and semi-official data from Chinese newspapers. In Section II, wholesale price levels are compared between China and Japan to assess the overall price level while exploring differences in the price system. The paper notes that data on commodity prices in Mainland China are insufficient for detailed economic analysis, although they appear more abundant than in other socialist countries. It highlights discrepancies between wholesale market prices and those in transactions among state enterprises, along with a reported decrease in the share of the wholesale market. Additionally, it states that retail prices of rationed commodities are lower than those in the "free market," making the analysis using published data not comprehensive of the entire price system.